HUBUNGAN PERKAWINAN “Sirang So Sirang”(Pisah tidak Pisah) Pada Keluarga Etnis Batak Toba Kristen Di Kandis Kota Kabupaten Siak - Daniel Ostega Siahaan; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in Kandis City of Siak Regency with the aim to obtain information about Marriage Relationship "Sirang so Sirang" In Ethnic Batak Toba Kristen family in Kandis City. Some of the problems in this research are (1) How is the process of "Sirang so Sirang" (Pisah tidak Pisah) occurring in the marital relationship of Ethnic Batak Toba Kristen family? (2) Who are the families of ethnic Batak Toba Christians who make a marriage relationship "Sirang so Sirang" (Pisah tidak Pisah)? (3) What are the benefits and disadvantages that occur with the relationship of Marriage "Sirang so Sirang" (Pisah tidak Pisah) in the Ethnic Batak Toba Christianity ?. The title of this research is:"MARRIAGE RELATIONSHIP" Sirang So Sirang "(Pisah tidak Pisah) In Family Ethnic Toba Batak Christian In Kandis City Siak Regency". The research is done to know how the process of the happening of Sirang so Sirang in the marriage relationship of Ethnic Batak Toba Christian family and anyone who do the marriage relationship and know the benefit and the loss that happened with the marriage relationship Sirang so Sirang in Ethnic Batak Toba Kristen family. In this study subjects who got until the data saturated (Snowball) amounted to 10 people. Those who are the subject are those who know and experience and are directly involved. The data were collected by interview, observation, and documentation. Interviews conducted were in-depth interviews. After doing this research, marriage relationship sirang so sirang in Toba Christian Batak family is the choice taken by both partner because where adat and religion adopted is not allowed divorce, and also involves both family member so that it is considered as a disgrace both big family because custom parties have been determined through partuturan, tarombo, and parhundulan position. Of these problems have more and have negative impact. The work that can be done for this problem is for couples to appreciate and enjoy the wisdom of marriage in Christianity as a sacred and sacred marriage so that for each couple can commit to the marriage that has been undertaken.Keywords: Relationships, Family, Batak Toba, Kristen, Sirang so Sirang